Three isoflavones from Derris scandens (Roxb.) Benth and their cancer chemopreventive activity and in vitro antiproliferative effects. (July 2020) - Ito, Chihiro; Matsui, Takuya; Miyabe, Kikuko; Hasan, Choudhury M.; Rashid, Mohammad A.; Tokuda, Harukuni; Itoigawa, Masataka
Abstract: Three undescribed isoflavones, derriscandenon A, B, and C, together with seven known isoflavones were isolated and structurally characterized during a study of the chemical constituents in the leaves of Derris scandens (Roxb.) Benth (Leguminosae, Fabaceae) collected in Bangladesh. The inhibitory activity of the compounds against activation of Epstein-Barr virus antigen (EBV-EA) by 12- O -tetradecanoylphorbo-13-acetate (TPA) was measured to identify possible chemopreventive agents. Mild inhibitory effects (IC50 278–290 mol ratio/32 pmol TPA) against EBV-EA induction compared with curcumin (IC50 341 mol ratio/32 pmol TPA) were observed for four known compounds (lupalbigenin, isopalbigenin, glyurallin, and isangustone A). Next, we focused on antitumor effects and investigated cell viability, cell proliferation, and mitochondria membrane potential by using an MTT assay, a live cell monitoring system, and fluorescence staining. Of the seven isoflavones tested for cell viability, a dose-dependent decrease in cell viability was observed for four isoflavones (derriscandenon B and C, derrubone, and glyurallin) in KB cells and two compounds (derriscandenon B and isochandaisone) in NALM6-MSH+ cells. In addition, the proliferation of KB cells was significantly inhibited by these four compounds at a concentration of 5 μM. The mitochondria membrane potentials of KB cells treated with derriscandenon C, derrubone, and glyurallin at the IC50 concentration were decreased by about 55%, whereas undescribed compound derriscandenon B had no effect. Our results show that some of the compounds isolated from D. scandens may be suitable as seed compounds for cancer prevention and therapy. Graphical abstract: Image 1 Highlights: Ten isoflavones were isolated from dried Derris scandens leaves. Three undescribed isoflavones, derriscandenon A, B, and C were identified. Some of the isolated isoflavones showed chemopreventive activity. Derriscandenon B inhibited cell proliferation of KB and NALM6-MSH+ cells.